2019
DOI: 10.1007/s11306-019-1486-5
|View full text |Cite
|
Sign up to set email alerts
|

Keeping the shape of plant tissue for visualizing metabolite features in segmentation and correlation analysis of imaging mass spectrometry in Asparagus officinalis

Abstract: Introduction Matrix-assisted laser desorption/ionization−imaging mass spectrometry (MALDI−IMS) is a powerful approach for visualizing the localization of metabolites. Objectives A method to keep the shape of plant tissue needs to be developed for MALDI−IMS. Methods The method was developed using transfer tape and double-sided conductive tape. Results MALDI−IMS analysis using the developed method enabled to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…One advantage of the presented approach was the use of copper foil tape to adhere the cryofilm to the target slide. Previous studies have utilised double‐sided carbon tape, such as that used in the mounting of EM tissue sections, while a recent study in plants has also reported the use of copper foil tape to adhere tape‐transferred sections to MALDI targets . The carbon tape surface is not flat and contains frequent pits of varying sizes that can create variable ion signal in a MALDI mass spectrometer due to the fixed nature of the laser focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One advantage of the presented approach was the use of copper foil tape to adhere the cryofilm to the target slide. Previous studies have utilised double‐sided carbon tape, such as that used in the mounting of EM tissue sections, while a recent study in plants has also reported the use of copper foil tape to adhere tape‐transferred sections to MALDI targets . The carbon tape surface is not flat and contains frequent pits of varying sizes that can create variable ion signal in a MALDI mass spectrometer due to the fixed nature of the laser focus.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, stabilisation of the tissue section prior to cutting, by using a tape transfer system has been useful for the collection of fresh frozen sections from some tissue types. Recently, methods for collection and MALDI‐IMS analysis of plant tissue sections using tape transfer were reported. Importantly, while the transfer tape is nonconductive, analysis of small molecules and metabolites was possible using MALDI‐FT‐ICR mass spectrometry, for which the use of a conductive target plate is not required.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in MS imaging (MSI) techniques (Mhlongo et al, 2018) have made it possible to map metabolites in intact plant tissues at sub-cellular level and connect the spatial complexity of the plant molecular organization to phenotypical features. Some techniques that have been hyphenated with MSI for imaging metabolites in plant specimens are matrix-assisted laser desorption/ionization (MALDI) and laser ablation electrospray ionization (LAESI) (Etalo et al, 2015;Nakabayashi et al, 2019). However, these approaches have not yet been utilized in ENMplant interaction studies.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…There is also a method to transfer only the tissue from the film to the glass slide using an ultraviolet light source, but this requires a very advanced technique and specialized equipment [58]. Recently, Nakabayashi et al [59] reported a technique to directly transfer a prepared section from a film to ITO-coated glass slides, which improves sample preparation for plant tissues with a high water content.…”
Section: Sectioningmentioning
confidence: 99%